1983
DOI: 10.1099/00207713-33-4-777
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Vibrionaceae Species by Their Cellular Fatty Acid Composition

Abstract: The cellular fatty acid compositions of 10 Vibrio species, two Aeromonas species, three Photobacterium species, Plesiomonas shigelloides, and Escherichia coli were determined by using capillary gas-liquid chromatography (GLC). The major fatty acids in all Vibrionaceae species and E. coli were hexadecenoic, hexadecanoic, and octadecenoic acids. Qualitative and quantitative differences in hydroxy, branched, and cyclopropane fatty acids and in isomers of unsaturated 16-and 18-carbon acids were used to divide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
2
3

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 20 publications
5
42
2
3
Order By: Relevance
“…Both novel Vibrio species represented by the 19 isolates examined in this study shared the main phenotypic and chemotaxonomic features of the genus Vibrio (Lambert et al, 1983;Farmer & Hickman-Brenner, 1992;Bertone et al, 1996). They were facultatively anaerobic, oxidasepositive and showed prolific growth on thiosulfate/citrate/ bile salts/sucrose agar (TCBS).…”
Section: Resultsmentioning
confidence: 53%
“…Both novel Vibrio species represented by the 19 isolates examined in this study shared the main phenotypic and chemotaxonomic features of the genus Vibrio (Lambert et al, 1983;Farmer & Hickman-Brenner, 1992;Bertone et al, 1996). They were facultatively anaerobic, oxidasepositive and showed prolific growth on thiosulfate/citrate/ bile salts/sucrose agar (TCBS).…”
Section: Resultsmentioning
confidence: 53%
“…The fatty acid pattern of strain F1F6 showed a number of features which appear to be shared by the limited number of strains belonging to the Campylobacter-Helicobacter-Arcobacter complex which have been studied with respect to their fatty acid composition (3,14,20). All of the orgapisms examined contained 14:0, 16:0, 18:0, and 18:lw7c, a combination which appears to be distinctive within the Proteobacteria.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, Urdaci et al (1990) and Bertone et al (1996) reported that 16 : 1, 16 : 0 and 18 : 1 were the major fatty acids in the Vibrio species they tested, 16 : 1 being predominant. Cyclopropane acid (17 : 0 cyclo), which occurs, for instance, in Photobacterium species (Lambert et al, 1983), was not detected in strain RE35F\12 T . Secondly, the cellular polyamine pattern of RE35F\12 T was characterized by the presence of the triamine sym-norspermidine (Vybiral et al, 1999), a compound commonly found in Vibrio species (Yamamoto et al, 1983 ;Hamana, 1997).…”
Section: Abbreviationmentioning
confidence: 93%
“…First of all, the major cellular fatty acids of the bacterium are 16 : 1ω9c (30n7 %), 16 : 0 (19n0%) and 18 : 1trans9, cis11 (16n5 %) (Vybiral et al, 1999). This signature is characteristic of Gram-negative bacteria, and a ratio of 16 : 1 (higher than 16 : 0) is also typical for the family Vibrionaceae (Bøe & Gjerde, 1980 ;Lambert et al, 1983). Moreover, Urdaci et al (1990) and Bertone et al (1996) reported that 16 : 1, 16 : 0 and 18 : 1 were the major fatty acids in the Vibrio species they tested, 16 : 1 being predominant.…”
Section: Abbreviationmentioning
confidence: 99%